Comparison between Captopril and Imidapril in Relation to Their in Vitro Effects on Tracheal Tissue (Medical Forum Monthly, 2024)
Objective: To observe two drugs (captopril and imidapril) action on smooth muscle tone of trachea and to facilitate safe and rational use of ACE inhibitors, particularly in patients with chronic obstructive airway disease.Study Design: Comparative controlled in-vitro experimental Study.Place and Duration of Study: This study was conducted at the Pharmacology Department, Army Medical College, Rawalpindi from December 2012 to May 2013.Materials and Method: First the effect of bradykinin acetate on the smooth muscle of trachea has been observed. Cumulative concentration-effect relationship was studied with different concentrations of bradykinin on the smooth muscle starting with 22µg to 132 µg/dl. The method was done again with captopril 10-5 M concentration and imidapril 10-5M respectively. In second set of experiments cumulative concentration-response curves were prepared by increasing concentrations of captopril and imidapril separately with fixed concentration of bradykinin 66 µg/dl. Results: Dose related vacillating contraction of smooth muscle of trachea is produced by bradykinin. The average value of effect received with 132 µg/dl of bradykinin in the presence of captopril was 51.33 ± 2.79 and in the presence of imidapril was 25 ± 7.26. All these ACE inhibitors displaced the concentration effect curves of bradykinin to left and upward. On comparison among themselves it was observed that imidapril produced least enhancement of tracheal contraction. Similar results were produced by second set of experiments. Conclusion: Imidapril is found to cause least enhancement of contraction caused by bradykinin on tracheal muscle. Further clinical trials may be conducted to establish the differential effects of various clinically used ACE inhibitors on the respiratory passages in hypertensive patients concomitantly suffering from COAD.